Staff and clinic protection during COVID pandemic - Vinod Hanumanthu; Raihan Ashraf; Rashmi Sarkar; Muthu Sendhil Kumaran (Wolters Kluwer Medknow Publications, 2020)
The impact of novel coronavirus pandemic (COVID-19) on the healthcare system has been devastating and the medical fraternity is facing challenges to tackle this catastrophic outbreak. With regard to dermatology practice, we review various outbreak response measures to be followed by the dermatology staff at clinic in constrained environment. Preventive measures like social distancing, hand hygiene practices and protective measures such as introduction of personal protective equipment (PPE) for staff, standardization of clinical guidelines and continuing medical services via teleconsultation are recommended. Physical consultation has been limited to emergency-based services. Although teledermatology would never replace physical consultation, it might serve as an adjunctive role in providing adequate services to the non-emergent conditions and minimizes the risk of exposure of both doctors and patients. Non-urgent visits of the patients are being discouraged and elective dermatology procedures are being postponed. Dermatologists should also recognize and educate health care workers about primary cutaneous features of COVID-19 as well possible dermatological side effects arising from prolonged usage of PPE and hand hygiene practices. Limited office-based and in-patient services with a parallel increase in teledermatology consultations will allow effective dermatologic care and services to the public while ensuring minimum transmission of the virus.